Concepções e práticas de territorialidade: avaliação das pesquisas de pós-graduação stricto sensu na área interdisciplinar da Capes a partir dos estudos sociais da ciência e tecnologia (ESCT) - Montero Castillo, Rosanna (2023)
The stricto sensu postgraduate, at the master's and doctoral level, constitute the set of teaching-learning processes aimed at guaranteeing a greater preparation of university graduates, in correspondence with technical-scientific advances that allow responding, through scientific research to social needs. In this sense, the present study aims to evaluate the territoriality, in terms of concepts and practices, in stricto sensu postgraduate research in the interdisciplinary area of CAPES from the Social Studies of Science and Technology (ESCT). It is developed from a theoretical-methodological framework based on the critical perspective of the ESCT and the dialectical historical materialism (MHD), fundamental to understand the social transformations that are constituted through the most varied processes, as is the case of the territoriality. The methodology consisted of a bibliometric analysis in two databases: one, of international reference, SCOPUS, and the other, of national reference, in the Catalog of Theses and Dissertations of CAPES – an institution that plays a fundamental role in the expansion and consolidation of stricto sensu postgraduate studies in Brazil – in order to know the current state of research on Territoriality. It was verified that the object under study has a trajectory of more than 34 years of research; theses represent about 23%, and dissertations concentrate 73% of the scientific productions in the nine academic areas defined by CAPES, with the highest incidence in the areas of Human Sciences, Multidisciplinary Sciences and Applied Social Sciences. With the previous results, a content analysis of the theses and dissertations developed in the area was carried out, focused on the dimensions: Physical/Natural, Symbolic/Cultural, time-space-territory relationship, in addition to identifying the territorial practices that they use. social actors to transform their reality (carried out by capitalist agents and/or insurgent spatial practices). The results showed the importance of Territoriality, verifying that there is a need for researchers to become aware of the research process on the object under study, at the same time that they adopt methodological strategies, procedures, categories and concepts that allow generating adequate responses to the goals they set. A concept on Territoriality was generated based on the research studied, and it was understood that it is born and is permeated by human interactions, evolves, adapts and marks patterns of change in the needs of new research, which makes it a dynamic conception, not finished and determined by the context, historical moment and conceptions of those who analyze it. In addition to the objectives, it was observed in the evaluated theses and dissertations that there are: 1) the need to deepen Decolonial studies as an expansion of STS studies. 2) little evidence of new concepts in the study area, and 3) absence of new strategies, practices, or methodological processes.